Goryeocrinus pentagrammos n. gen. n. sp. (Rhodocrinitidae; Diplobathrida), the first record of camerate crinoid from the Middle Ordovician (Darriwilian) of South Korea (East Gondwana). (March 2023) - Park, Hyeonmin; Lee, Dong-Chan
Abstract: Goryeocrinus pentagrammos n. gen. n. sp. from the Jigunsan Formation of South Korea is described and is the first diplobathrid recorded from Middle Ordovician (middle Darriwilian) strata of East Gondwana. Phylogenetic analyses suggest that G . pentagrammos n. gen. n. sp. is a member of the paraphyletic Rhodocrinitidae of the Diplobathrida and most closely related to Paradiabolocrinus from the Late Ordovician (Sandbian) of Laurentia. Goryeocrinus pentagrammos n. gen. n. sp. is characterized by having a pentameral, flat bowl-shaped calyx, a conspicuous pentagrammatic ridge formed by bifurcated median ray ridge and pentagonal basal ridge, at least two interradials in the first row of regular interrays, an anitaxial ridge originating from the CD interray but close to the C ray radial, and lacking intrabrachials and interradials between secundibrachials. The occurrence of G . pentagrammos n. gen. n. sp. from South Korea (East Gondwana) drastically expands the Ordovician paleogeographic range of camerates, which otherwise have been recorded from Laurentia, West Gondwana, Avalonia, and Baltica. UUID: http://zoobank.org/a5f8fc12-25a5-4e7c-92e8-bf3ea07c3ba3